Love in the time of Disney princesses - Beloso, Lorena; Fullana, Marisol (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2019)
The “Wonderful Disney World”, from its Princesses, proposes female stereotypes as possible answers to the Freudian question about what a woman wants. From the first appearance to the present, these princesses were modifying their positions and countenance, according to the discourse of the prevailing master. In the same way their relationship to men was transformed, and the place they give to love. Since the 30s, with the model of mother and housewife, going through the 60s with sexual liberation, and the first feminist movements, to the present where feminisms take center stage, women were reinventing themselves, and with it their ties , to the other, and consequently to the Other.